Distance and Private Information in Lending - Agarwal, Sumit; Hauswald, Robert (Review of Financial Studies, 2010)
We study the effects of physical distance on the acquisition and use of private information in informationally opaque credit markets. Using a unique data set of all loan applications by small firms to a large bank, we show that borrower proximity facilitates the collection of soft information, leading to a trade-off in the availability and pricing of credit, which is more readily accessible to nearby firms albeit at higher interest rates ceteris paribus. Analyzing loan rates and firms’ decision to switch lenders provides further evidence for banks’ strategic use of private information. However, distance erodes our lender’s ability to collect proprietary intelligence and to carve out local captive markets, suggesting that the requisite soft information is primarily local.